Operando Li metal plating diagnostics via MHz band electromagnetics - Ishigaki, Masanori; Ishikawa, Keisuke; Usuki, Tsukasa; Kondo, Hiroki; Komagata, Shogo; Sasaki, Tsuyoshi (Nature communications, 2023)
A nondestructive detection method for internal Li-metal plating in lithium-ion batteries is essential to improve their lifetime. Here, we demonstrate a direct Li-metal detection technology that focuses on electromagnetic behaviour. Through an interdisciplinary approach combining the ionic behaviour of electrochemical reactions at the negative electrode and the electromagnetic behaviour of electrons based on Maxwell’s equations, we find that internal Li-metal plating can be detected by the decrease in real part of the impedance at high-frequency. This finding enables simpler diagnostics when compared to data-driven analysis because we can correlate a direct response from the electronic behaviour to the metallic material property rather changes in the ionic behaviour. We test this response using commercial Li-ion batteries subject to extremely fast charging conditions to induce Li-metal plating. From this, we develop a battery sensor that detects and monitors the cycle-by-cycle growth of Li-metal plating. This work not only contributes to advancing future Li-ion battery development but may also serve as a tool for Li-metal plating monitoring in real-field applications to increase the useable lifetime of Li-ion batteries and to prevent detrimental Li-metal plating. Internal growth of Li-metal deposition is critical for evaluating the state of safety in lithium-ion batteries. Here the authors show a Li-metal detection method utilizing high-frequency electromagnetics, which can be assembled as a sensor for monitoring cycle-by-cycle growth of Li-metal plating.